309 Highly Sensitive Detection of the IDH1 R132H Mutation in the Plasma of Glioma Patients. Issue Volume 65:Issue CN(2018)Supplement 1 (16th August 2018) - Balaj, Leonora; Carter, Bob S; Castellanos-Rizaldos, Elena; Peruzzi, Pier Paolo; Chan, Dalin; Zhang, Xuan; Skog, Johan
Abstract: INTRODUCTION: Recurrent isocitrate dehydrogenase (IDH) gene mutations are found in up to 80% of low-grade gliomas and 20% of secondary glioblastomas, identifying tumors with distinct etiology, associated genetic alterations, and overall natural history. Detection of the mutation prior to surgery would aid in the management of care, including the extent of surgical resection and treatment regimen. Cell-free DNA (cfDNA) is released into biofluids from dying cellular processes and has been used to detect mutations in plasma from cancer patients. Extracellular vesicles are actively released from living cells into plasma, and combining these 2 sources of nucleic acids can increase sensitivity. METHODS: We developed a plasma-based assay that combines exo nucleic acid (NA) and cell-free DNA to detect R132H with as little as 1 to 2 mL of input material using ddPCR. The test was optimized to detect single copies of the mutation and then, its clinical performance was assessed on an interim cohort of 17 clinical samples for which matched tissue data were available. RESULTS: In this study, we detected R132H in the patient samples analyzed with 53% sensitivity and 100% specificity. This result is similar to the sensitivity we previously published using exosomes from cerebrospinal fluid; however, plasma is a much more accessible biofluid for diagnostics. In addition, we postulate that the ratios of DNA to RNA mutations may potentially indicate the disease status where a high level of the mutation at the DNA level indicates tumor cell death, while a high level of mutation at the RNA may indicate tumor growth and progression CONCLUSION: We report a novel platform to capture both exoNA and cfDNA in circulation in plasma to detect rare copies of R132H from patients with gliomas. Combining these 2 sources of information may enable a more sensitive diagnosis and tracking of the course of the disease.